LAYANAN KONSELING INDIVIDU DENGAN PENDEKATAN REBT (RATIONAL EMOTIVE BEHAVIOR THERAPY) DALAM MENANGANI KORBAN KEKERASAN DALAM RUMAH TANGGA (Studi Kasus di Dinas Pemberdayaan Perempuan dan Perlindungan Anak Kabupaten Lampung Selatan) - Hasnayah, Fathatun; Setiawati , Rini; tanjung, Noffiyanti (Universitas Islam Ahmad Dahlan, 2025)
Domestic violence (DV) is a serious social problem and continues to be a concern, including in South Lampung District. The South Lampung Regency Women's Empowerment and Child Protection (PPPA) Office plays an important role in providing services to victims of domestic violence. One of the efforts made is to provide individual counseling services with the REBT approach. The purpose of this study was to examine individual counseling services with the REBT approach in dealing with victims of domestic violence at the South Lampung Regency Women's Empowerment and Child Protection Office. The research method used is qualitative, descriptive qualitative, which means examining the current status of human groups, objects, conditions, systems of thought, and classes of events. The results obtained are, there are three indicators of the causes of domestic violence, namely, the existence of an unbalanced power relationship between husband and wife, economic dependence, and violence as a conflict resolution. The REBT approach in individual counseling at the PPPA Office of South Lampung Regency is an effective method in helping victims of domestic violence overcome trauma and rebuild self-confidence.